1984
DOI: 10.1002/jpln.19841470617
|View full text |Cite
|
Sign up to set email alerts
|

Transformations and effects of urea derivatives in soil

Abstract: The application of urea phosphate, urea nitrate and thoiurea to a silty clay soil from Nile Delta (pH 7.4, 1,9% CaCO3) inhibited soil urease activity if compared to urea. The nitrification process of ammonia formed from urea hydrolysis was retarded. The use of these urea derivatives eliminated nitrite accumulation and greatly retarded nitrate formation with increased recovery of urea-N throughout the experimental period. Gaseous losses of urea-N as ammonia or by denitrification were reduced. These derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(5 reference statements)
2
8
0
Order By: Relevance
“…New designs, based on urea cocrystals, recently emerged following evidence that urea coordination compounds can reduce N losses from soils. For example, agricultural field tests with NH 4 Cl or ZnSO 4 have been shown to reduce NH 3 losses from the soil and improve overall nitrogen uptake efficiency when compacted with urea. , Inhibition of urea reactivity by inorganic acids, such as phosphoric acid, was also shown to decrease NH 3 emissions up to 50% from soils fertilized with urea phosphate ionic cocrystal. , Significant decrease of NH 3 emissions for urea·MgSO 4 cocrystals was similarly observed, but the proposed reaction mechanisms were inconclusive. More recent work has expanded this approach by designing urea cocrystals with salts containing Ca 2+ and Mg 2+ obtained from parent ionic compounds or via reactive mechanochemistry using the appropriate minerals. , This approach was further extended to synthesize double salts of NH 4 + containing HPO 4 2– , Ca 2+ , or Mg 2+ ions [Ca­(NH 4 ) 2 (HPO 4 ) 2 ·H 2 O dimorph B and Mg­(NH 4 ) 2 (HPO 4 ) 2 ·4H 2 O dimorph A] as well as their struvite equivalents [Ca­(NH 4 )­(PO 4 )·H 2 O and Mg­(NH 4 )­(PO 4 )·6H 2 O] .…”
Section: Introductionmentioning
confidence: 99%
“…New designs, based on urea cocrystals, recently emerged following evidence that urea coordination compounds can reduce N losses from soils. For example, agricultural field tests with NH 4 Cl or ZnSO 4 have been shown to reduce NH 3 losses from the soil and improve overall nitrogen uptake efficiency when compacted with urea. , Inhibition of urea reactivity by inorganic acids, such as phosphoric acid, was also shown to decrease NH 3 emissions up to 50% from soils fertilized with urea phosphate ionic cocrystal. , Significant decrease of NH 3 emissions for urea·MgSO 4 cocrystals was similarly observed, but the proposed reaction mechanisms were inconclusive. More recent work has expanded this approach by designing urea cocrystals with salts containing Ca 2+ and Mg 2+ obtained from parent ionic compounds or via reactive mechanochemistry using the appropriate minerals. , This approach was further extended to synthesize double salts of NH 4 + containing HPO 4 2– , Ca 2+ , or Mg 2+ ions [Ca­(NH 4 ) 2 (HPO 4 ) 2 ·H 2 O dimorph B and Mg­(NH 4 ) 2 (HPO 4 ) 2 ·4H 2 O dimorph A] as well as their struvite equivalents [Ca­(NH 4 )­(PO 4 )·H 2 O and Mg­(NH 4 )­(PO 4 )·6H 2 O] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, agricultural field tests with NH 4 Cl or ZnSO 4 have been shown to reduce NH 3 losses from soil and improve overall nitrogen uptake efficiency when compacted with urea . The inhibition of urea reactivity by organic or inorganic acids, such as phosphoric acid, was shown to decrease NH 3 emissions up to 50% from soil fertilized with urea phosphate ionic cocrystal . Von Rheinbaben and Fenn et al showed a significant decrease in NH 3 emissions for applied or reactively formed urea·Mg­(Ca)­SO 4 (or presumably urea adducts with CaCl 2 and Ca­(NO 3 ) 2 formed in situ in soil), but the reaction mechanisms put forth were inconclusive, as other authors showed that sulfate salts were not effective NH 3 emission regulators .…”
Section: Introductionmentioning
confidence: 99%
“…A conceptually interesting approach in obtaining novel EEF is the alteration of urea’s reactive properties by confining it in a single molecular crystal unit with the inorganic acids or their metal salts, such as Ca or Mg phosphates, sulfates and nitrates. Reports exist where a molecular crystals of urea and phosphoric or nitric acid was shown to result only 0.7% nitrogen loss as ammonia as opposed to up to 61.1% of soil treated with urea only, , which suggests that major improvements to the global nitrogen cycle are achievable. , Additionally, urea molecular ionic cocrystals with inorganic Mg and Ca salts also contain other primary and secondary nutrients, such as P, Ca, Mg and S, which are necessary for a balanced nitrogen uptake . The classical way of obtaining these crystalline Ca and Mg salt–urea ionic cocrystal materials is their precipitation from saturated aqueous solutions via heating and slow evaporation. , Mechanosynthesis, on the other hand, is a dry preparation method with plenty of opportunities in clean synthesis that have already been applied in EFF engineering, but very few compounds made were well-defined crystalline materials, such as KMgPO 4 , NH 4 MgPO 4 and layered double hydroxides (LDH), Mg–Al–NO 3 (Mg:Al = 3:1) .…”
Section: Introductionmentioning
confidence: 99%